REFLECTIONS OF / AND OTHERNESS IN MINEIRINHO: CLARICE LISPECTOR AND MAURITS CORNEILS ESCHER - Pando, Monelise Vilela [UNESP] (Univ Fed Goias, Campus Catalao, 2019)
There are many studies around the work of Clarice Lispector, and among them, there are many dedicated to the search for relations between literature and painting. In this sense, we intend to carry out a course that can demonstrate how the visual metaphors of the Dutch graphic designer Maurits Cornelis Escher (1898-1972), can build parallels capable of illuminating the reading process of the narrative arranged by Clarice Lispector (1920-1977), in the tale Mineirinho (1964), once there are many entries and possible duplication to access the reading of the text of Lispector. This work seeks questions such as the paradoxical disposition of otherness, established by the narrator when he judges Mineirinho; the development of narrative processes of mirror games; and finally, a type of dramatic conflict that seems to have no end, or solution. To do this, we will rely on the readings of Clarice Lispector's critical fortune, thinking of the concept of structural homologies, so that we can verify how certain artistic effects are established in each of these languages of different semiotic systems: literature and painting.
Keywords: Clarice Lispector; Mr. C. Escher; Homological Relations; Literature and painting